Intraocular pressure in a clinical population: a retrospective study - Norhani Mohidin; Norsuhana Abd Wahab (Universiti Kebangsaan Malaysia, 2010)
A retrospective study was carried out to determine the distribution of intraocular pressure in normal patients who came for vision problems at the Optometry Clinic, Universiti Kebangsaan Malaysia (UKM) Kuala Lumpur Campus, and to determine the differences in intraocular pressure with respect to age, gender and race. The cohort consisted of 148 subjects divided into five groups with age ranged from 10 to 59 years. The inclusion criteria were, subjects had no sistemic or ocular disease, subjects were not taking any medication, visual acuity was 6/6 or better, refractive errors < ±6.00D, astigmatism < 2.00D, anisometropia <2.00D, and mean intraocular pressure measured using the X-PERT tonometer and taken between 9 am to 2 pm. Statistical analysis (ANOVA) showed the mean intraocular pressure without consideration for age, race or gender was 12.6 mmHg (SD ±2.5). There was no significant differences in intraocular pressure between right and left eyes, between different age groups and between different genders. However, the intraocular pressuse for the Chinese was found to be significantly higher than the Malays. It was found that the intraocular pressure of patients who came for vision problems at the Optometry Clinic UKM follows a normal distribution and there was no significant diference found between right and left eyes, between different age groups and genders. Race seemed to contribute to the differences in intraocular pressure.